2017
DOI: 10.1016/j.jgr.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Quality and characteristics of fermented ginseng seed oil based on bacterial strain and extraction method

Abstract: BackgroundIn this study, the fermentation of ginseng seeds was hypothesized to produce useful physiologically-active substances, similar to that observed for fermented ginseng root. Ginseng seed was fermented using Bacillus, Pediococcus, and Lactobacillus strains to extract ginseng seed oil, and the extraction yield, color, and quantity of phenolic compounds, fatty acids, and phytosterol were then analyzed.MethodsThe ginseng seed was fermented inoculating 1% of each strain on sterilized ginseng seeds and incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Previously, ten phenolic/or flavonoid profiles (such as salicylic acid, vanillic acid, ascorbic acid, p -coumaric acid, ferulic acid, caffecic acid, gentisic acid, p -hydorxybenzoic acid, maltol, cinnamic acid, protocatechuic acid, syringic acid, and quercetin) were investigated in fresh and/or processed ginseng/or ginseng seed [ 16 , 24 , 28 , 31 ]. Chung et al [ 32 ] reported that Korean ginseng contains p -coumaric acid, which is especially highest in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, ten phenolic/or flavonoid profiles (such as salicylic acid, vanillic acid, ascorbic acid, p -coumaric acid, ferulic acid, caffecic acid, gentisic acid, p -hydorxybenzoic acid, maltol, cinnamic acid, protocatechuic acid, syringic acid, and quercetin) were investigated in fresh and/or processed ginseng/or ginseng seed [ 16 , 24 , 28 , 31 ]. Chung et al [ 32 ] reported that Korean ginseng contains p -coumaric acid, which is especially highest in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…However, the proportion of USFAs with respect to SFAs detected during food processing steps increased. A previous study reported that fermentation strain did not affect total FAs [ 27 ]. Our results slightly differ from previous data in that the total FA content of ginseng seeds and MCGS did not change according to the fermentation process [ 1 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…These data are in agreement with another study that indicated that phytosterol content in ginseng seed oil obtained by supercritical CO 2 fluid extraction was greater than in that obtained by conventional methods such as solvent extraction and compression extraction [ 26 ]. Fermented ginseng seed oil obtained by supercritical CO 2 fluid extraction also showed significantly higher phenolic compound and phytosterol contents compared with that obtained by compression extraction or solvent extraction [ 35 ]. Therefore, SFE using CO 2 appears to be the optimum extraction method for obtaining RGO.…”
Section: Extraction Of Rgomentioning
confidence: 99%
“…The level of unsaturated fatty acids in RGO is comparable to that in Korean fermented ginseng seed oil and in American ginseng ( Panax quinquefolius L.) seed oil. However, the predominant unsaturated fatty acid in RGO is the polyunsaturated linoleic acid, while a monounsaturated fatty acid, oleic acid, is predominant in both Korean and American ginseng seed oils [ 35 , 37 , 38 ]. In addition, RGO contains significant amounts of oleic acid, linolenic acid, and cis -11,14-eicosatyrienoic acid, and also contains other unsaturated fatty acids such as erucic acid, cis -13,16-docosadienoic acid, nervonic acid, cis -11-eicosenoic acid, palmitoleic acid, gamma-linolenic acid, arachidonic acid, and cis -10-heptadecenoic acid [ 27 , 37 ].…”
Section: Chemical Composition Of Rgomentioning
confidence: 99%